유방암 세포에서 ER-associated degradation 억제를 통한 Eeyarestatin1의 paraptosis 유도 - 서민지 (The Graduate School, Ajou University, 2017)
Endoplasmic reticulum-associated protein degradation (ERAD) is a cellular pathway which targets misfolded protein of the endoplasmic reticulum (ER) for ubiquitination and subsequent degradation by proteasome. In this study, I investigated the anti-tumor effects of Eeyarestatin1 (Eer1), a potent inhibitor of ERAD, in various breast cancer cells. I found that treatment of breast cancer cells with Eer1 induced the dilation of mitochondria and the ER without any apoptotic characteristics. Prior to cell death, Eer1 treatment induced the accumulation of poly-ubiquitinated proteins as well as the proteins associated with ER stress and Eer1-induced accumulation of these proteins was completely blocked by cycloheximide. In addition, Eer1 treatment induced the activation of both JNKs and ERKs. Taken together, these results suggest that Eer1 treatment kills breast cancer cells via induction of paraptosis. Furthermore, I found that following Eer1 treatment the phosphorylation levels of eIF2α at Serine 51 were progressively reduced and pretreatment with salubrinal, an inhibitor of eIF2α phosphatase, markedly attenuated Eer1-induced vacuolation and cell death. In addition, overexpression of the non-phosphorylatable mutant eIF2α (with a mutation at serine 51 to alanine; S51A) markedly delayed them. Collectively, these results indicate that eIF2α dephosphorylation may critically contribute to Eer1-induced paraptosis in breast cancer cells.
학위논문(석사)--아주대학교 일반대학원 :의생명과학과,2017. 2
Keywords: Eer1; breast cancer; endoplasmic reticulum; mitochondria; paraptosis; ERAD; eIF2α